2022
DOI: 10.1111/jeb.14078
|View full text |Cite
|
Sign up to set email alerts
|

New insights into Xenopus sex chromosome genomics from the Marsabit clawed frog X. borealis

Abstract: In many groups, sex chromosomes change frequently but the drivers of their rapid evolution are varied and often poorly characterized. With an aim of further understanding sex chromosome turnover, we investigated the polymorphic sex chromosomes of the Marsabit clawed frog, Xenopus borealis, using genomic data and a new chromosome‐scale genome assembly. We confirmed previous findings that 54.1 Mb of chromosome 8L is sex‐linked in animals from east Kenya and a laboratory strain, but most (or all) of this region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Additionally, the genetic linkages of sex chromosomes were different among several Pipidae species (Bewick et al, 2011;Cauret et al, 2020;Evans et al, 2022;Furman & Evans, 2016;Furman et al, 2020;Mitros et al, 2019;Roco et al, 2015;Uno et al, 2008bUno et al, , 2015. These findings indicate that Dmw in X. laevis is younger than expected and that diversity in the origins of sex chromosomes results in frequent turnover of sex chromosomes and sex-determining genes, even in a single family, Pipidae.…”
Section: Diversity In the Sex Chromosome Origins In Amphibiansmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, the genetic linkages of sex chromosomes were different among several Pipidae species (Bewick et al, 2011;Cauret et al, 2020;Evans et al, 2022;Furman & Evans, 2016;Furman et al, 2020;Mitros et al, 2019;Roco et al, 2015;Uno et al, 2008bUno et al, , 2015. These findings indicate that Dmw in X. laevis is younger than expected and that diversity in the origins of sex chromosomes results in frequent turnover of sex chromosomes and sex-determining genes, even in a single family, Pipidae.…”
Section: Diversity In the Sex Chromosome Origins In Amphibiansmentioning
confidence: 87%
“…However, genomic and cytogenetic analyses of Pipidae species revealed that Dmw was retained only in X. laevis and other closely related species (Bewick et al, 2011; Cauret et al, 2020; Furman & Evans, 2016; Roco et al, 2015; Uno et al, 2008b). Additionally, the genetic linkages of sex chromosomes were different among several Pipidae species (Bewick et al, 2011; Cauret et al, 2020; Evans et al, 2022; Furman & Evans, 2016; Furman et al, 2020; Mitros et al, 2019; Roco et al, 2015; Uno et al, 2008b, 2015). These findings indicate that Dmw in X. laevis is younger than expected and that diversity in the origins of sex chromosomes results in frequent turnover of sex chromosomes and sex‐determining genes, even in a single family, Pipidae.…”
Section: Diversity In the Sex Chromosome Origins In Amphibiansmentioning
confidence: 99%
“…Depending on the questions and available genomic resources on given species/taxa, both approaches can detect sex‐determining regions and possible sex chromosome turnover events among closely related species. For instance, in this special issue: Using a combination of short‐read and long‐read sequencing, Evans et al (2022) and Duhamel et al (2022) perform a chromosome‐scale genome assembly in the Marsabit clawed frog and anther‐smut fungi, respectively. These approaches allow the study of intra‐specific variation of sex chromosome divergence in the frog and reveal independent chromosomal rearrangement in the mating‐type chromosomes of the fungi. With short‐read WGS and the help of existing reference genomes, Sigeman et al (2022) investigate the translocation nature of a novel neo‐sex chromosome in Sylvivoidea songbirds, whilst Rovatsos et al (2022) reveal a XX/XY sex determination system in a blind lizard and further identified a novel combination of homologous genes using the chicken X chromosome as reference. With short‐read whole‐genome pooled sequencing, Ansai et al (2022) and Jeffries et al (2022) investigate the sex‐determining regions and sex chromosome turnover across closely related fish taxa. With RAD‐seq, Keating et al (2022) and Meuser et al (2022) perform analysis in multiple individuals per sex to investigate possible sex‐determining regions and infer sex chromosome turnovers. …”
Section: Theme 1: Genomics and Methodological Advancesmentioning
confidence: 99%
“…It is not uncommon to find intraspecific variation in sex chromosome differentiation (see Rodrigues et al, 2015; Jeffries et al, 2018; Ma et al, 2018 in various frogs). Evans et al (2022) confirm that a 54.1 Mb sex‐linked region on the W chromosome in the east Kenyan population of the Marsabit clawed frog is not sex‐linked in the west Kenyan populations. This highlights a complex evolutionary trajectory of little differentiated, ‘young’ sex chromosomes and suggests that future work should focus on understanding the evolutionary dynamics of sex chromosomes and detection of sex‐determining genes in various frog groups (see review by Ma & Veltsos, 2021).…”
Section: Theme 3: Sex Chromosome Differentiation and Diversificationmentioning
confidence: 98%
“…Notably, to date, in >8,650 species of amphibians 16 , the widespread combination of poorly or undifferentiated sex chromosomes with large genome-sizes (see below) have caused a basic knowledge gap with only a single though very well-characterized amphibian master sex-determination gene known in a model species, the African clawed frog ( Xenopus laevis 11,17 ) and some related species 18 . Dm-w arose after (and perhaps in response to) tetraploidization, and has been lost secondarily in some tetraploid species 19 .…”
Section: Introductionmentioning
confidence: 99%